1994
DOI: 10.1161/01.cir.89.6.2509
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of atrial thrombus by transesophageal echocardiography does not preclude embolism after cardioversion of atrial fibrillation. A multicenter study.

Abstract: Background Transesophageal echocardiography (TEE) has been used recently to detect atrial thrombi before cardioversion of atrial arrhythmias. It has been assumed that embolic events after cardioversion result from embolism of preexisting atrial thrombi that are accurately detected by TEE. This study examined the clinical and echocardiographic findings in patients with embolism after cardioversion of atrial fibrillation despite exclusion of atrial thrombi by TEE.Methods and Results Clinical and echocardiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(116 citation statements)
references
References 31 publications
2
109
0
5
Order By: Relevance
“…Restoration of sinus rhythm provides numerous physiological benefits, 12) but as with most new therapies, direct-current CV also has adverse outcomes, including catastropic thromboembolism in up to 6.3 percent of patients who were not receiving anticoagulant therapy. 13) Nonrandomized studies where warfarin therapy was given for 3 to 4 weeks before CV led to an 80 percent reduction in CV-related thromboembolism, 14) providing the rationale for the use of this strategy for nearly three decades.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of sinus rhythm provides numerous physiological benefits, 12) but as with most new therapies, direct-current CV also has adverse outcomes, including catastropic thromboembolism in up to 6.3 percent of patients who were not receiving anticoagulant therapy. 13) Nonrandomized studies where warfarin therapy was given for 3 to 4 weeks before CV led to an 80 percent reduction in CV-related thromboembolism, 14) providing the rationale for the use of this strategy for nearly three decades.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the utility of TOE for thrombus detection in the LAA [13], a small number of thromboembolic events continue to occur even when no thrombus is detected in a pre-cardioversion [8] or LAA-occlusion setting (1-2%) [5,6]. Possible causes include absent or sub-therapeutic anticoagulation [14] and air embolism due to insufficient venting during LAA occlusion [5].…”
Section: Toe-guided Thrombus Detectionmentioning
confidence: 99%
“…Thrombus located in accessory or retroverted lobes might escape recognition in the usual TOE views, which may partially explain the small incidence of stroke despite TOE interrogation of the LAA prior to cardioversion [8]. Hence, a good understanding of LAA anatomy and orientation is important.…”
Section: Introductionmentioning
confidence: 99%
“…Using the two-dimensional beam of TEE in visualizing the three-dimensional anatomy of the LAA is analogous to using a searchlight to visualize the entire roof of a cave, which is technically difficult to achieve completely. Studies have shown that embolism may presumably occur after cardioversion of AF, despite apparent exclusion of a pre-existing atrial thrombus by TEE (6). Plasma D-dimer constitutes an antigen-antibody reaction to the dimeric final degradation product of a mature clot.…”
mentioning
confidence: 99%